Temperature dependence of the Helmholtz free energy of liquid alkali metals - Singh, BK; Singh, Sudhir (BIBECHANA, 2012)
The Gibbs-Bogoliubov variational method has been considered to study the Helmholtz free energy of liquid alkali metals (Na, K, Rb and Cs) as a function of temperature, using Heine Abarenkov type model potential with Hubbard-Sham exchange and correlation function. The computed values are in very good agreement with experimental observations. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7144 BIBECHANA 9 (2013) 7-12